Resveratrol treatment has neuroprotective effects and prevents cognitive impairment after chronic cerebral hypoperfusion. (July 2014) - Anastácio, Janine R.; Netto, Carlos A.; Castro, Cibele C.; Sanches, Eduardo F.; Ferreira, Daniele C.; Noschang, Cristie; Krolow, Rachel; Dalmaz, Carla; Pagnussat, Aline
<x content-type="archive" xml:space="preserve">Abstract</x> Objective: The present study investigated the neuroprotective effects of Resveratrol (RSV) in rats submitted to chronic cerebral hypoperfusion (CCH) in a model of permanent two-vessel occlusion (2VO). Methods: For this purpose, adult Wistar rats received daily i.p. injections of RSV (20 mg/kg) for 7 days, starting 1 hour after the 2VO procedure. Behavioral testing was run between the 30th and 45th days after the 2VO surgery. Accordingly, spatial working memory function in the Morris water maze was evaluated. At the end of the behavioral assessment (45th day post-surgery) part of experimental animals underwent transcardiac perfusion for histological analysis. Another group was euthanized on the 3rd, 14th, and 45th days post-surgery for nerve growth factor (NGF) evaluation. Results: Resveratrol treatment along 7 days after CCH significantly attenuated pyramidal cell death in the CA1 hippocampal subfield and prevented both spatial working and reference memory impairments. Our results revealed an enhancement of NGF expression 3 days after CCH in all ischemic animals. A late increase in hippocampal NGF levels was detected after 45 days only in CCH-RSV treated animals. Conclusions: Results presented here show morphological and functional neuroprotective actions of RSV treatment for CCH, as well as support the inducing effects of RSV on the expression of NGF and its possible association to the neuroprotective action in this rodent model of vascular dementia.